THE STUDY OF FRUCTOSE DESTRUCTION DYNAMICS IN THE PROCESS OF CUCUMBERS DIRECTED FERMENTATION - V. V. Kondratenko; O. Yu. Lyalina; N. E. Posokina; E. S. Tyrina; V. I. Tereshonok (Овощи России)
The process of the directed fermentation of cucumber ‘Vodoley’is studied with strains of lactic acid bacteria to improve the final product quality and reducing losses during storage. The objective of our studies was to investigate the dynamics of fructose destruction at the process of directed fermentation of cucumber using strains of lactic acid bacteria (microorganisms) and their choosing for this process. The following strains of lactic bacteria (LAB) were used: Lactobacillus brevis In the VCR-1309, VCR 536 Lactobacillus casei, Lactobacillus plantarum VKM V-578. To obtain comparable results, all experiments were performed on simulated medium. The raw material was homogenized and sterilized to make optimal condition for development of the target microorganism. The different strains of microorganisms were tested to detect the  degree of fructose destruction. The developed mathematical model adequately described the degree of fructose destruction at the process of treatment. Mathematical data processing on fructose destruction at the process of directed fermentation was performed using Microsoft Excel and SYSTAT TableCurve 2D. It is established that use of strain L. brevis was the most effective providing maximal efficiency according to the  criterion of intensity of fructose destruction at process of fermentation in cucumber where the maximal acceptable duration is 11-14 days to reach 92% of fructose destruction to asymptotic value. The strain L. brevis enabled to achieve the highest degree of fructose destruction, which, has presumably indicated the potential feasibility of using these lactic acid microorganisms.